THE INFLUENCE OF TRADITIONAL MARKETING AND DIGITAL MARKETING STRATEGIES ON PURCHASE INTENTION OF TABUNGAN EMAS PRODUCTS AT PT. PEGADAIAN, BITUNG - Purba, Marganda Nevira; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to analyze the influences of traditional and digital marketing strategies on purchase intention in Tabungan Emas products at PT Pegadaian Bitung. Through a quantitative approach, data was collected from 100 respondents consisting of Pegadaian customers who are active in social media and have age criteria of 20-60 years old and domiciled in Bitung City. The results showed that both traditional and digital marketing have a significant influence on purchase intention and have a positive influence. Traditional marketing strategies such as print advertising and exhibitions increase trust and product understanding, while digital marketing through information accessibility and interactive content successfully attracts consumer interest. This method was taken using a questionnaire using a 6-point Likert scale. It was found that traditional marketing and digital marketing proved to have a strong influence, where 51.5% of purchase intention was influenced by these two variables.   Keywords: Traditional Marketing, Digital Marketing, Purchase Intention